Development of an E-Worksheet Scientific Approach to Enhance Critical Thinking of 8th Grade Students - Prasetia, Endra; Sugiyarto, Sugiyarto (International Journal on Emerging Mathematics Education, 2023)
Probability is one of the materials that makes students find it challenging to engage with contextual problems. In fact, the critical thinking ability of students at Junior High School Muhammadiyah 1 Pundong on probability is relatively low; this is shown by the results of tests conducted by researchers. The cause of weak critical thinking is the learning model used by teachers during the learning process, namely the traditional learning model where teaching materials are not available which contain materials and exercises that students can use for independent learning. This research aims to develop an E-worksheet with a scientific approach to improve critical thinking skills. This research is research and development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The tools used in this research are validation tools from material and media experts, student response tools and pretest questions. Based on the validity test of E-worksheet products based on a scientific approach, it achieved an average of 4 in the competency category for media and 3.83 for material, while E-worksheet had an average of 94.18 in student responses in convenient terms. Based on the results of the comparative analysis of the averages presented, random E-worksheet material based on a scientific approach is effectively used in developing students' critical skills. Improving learning outcomes is supported by several features contained in the E-worksheet application. However, there are obstacles to using applications that are only used on Android phones rather than on other types of smartphones. However, this does not become an obstacle to the learning process.